Histopathological analysis of hysterectomy specimens: one year study - Baral, R; Sherpa, P; Gautam, D (Journal of Pathology of Nepal, 2017)
Backgound: The uterus is prone to develop several non-neoplastic and neoplastic conditions during the life time of a woman. The aim of this study is to study the histopathological features of varied uterine lesions, their profile and distribution of different lesions in relation of age. Materials and Methods: This is a histopathological database analysis of hysterectomy specimen of one year 2011/12 in Patan Hospital. The variables studied were age and histopathological diagnosis. SPSS version 16 was used as an analytical tool. Results: A total of 3576 histopathology samples were received in this period. There were 1173 gynaecology samples during this period out of which 22% (261 cases) were that of hysterectomy. Histopathology diagnosis showed Leiomyoma in 48.6% (127 cases), Adenomyosis was seen in 10.3% (27 cases), Endometrioid Adenocarcinoma was seen in 1.14% (3 cases). Conclusion: A large number of hysterectomy specimens had no significant findings. However, adenomyosis, leiomyomya and adenocarcinoma are also found which may be the cause of abnormal uterine bleeding.